SPHINCTER OCHSNER DYSKINESIA AS A CAUSE OF SUPERIOR MESENTERIC ARTERY SYNDROME - M. D. Levin (Вестник рентгенологии и радиологии)
Objective – to investigate the pathological physiology of superior mesenteric artery syndrome (SMAS). Material and methods. We selected 35 articles devoted to SMAS, which were published from 1990 to 2014, and performed radiometric analysis of X-rays, CT scans and MRI slices found in these articles. In pictures the narrowing in the third part of the duodenum was measured from the boundary of the expanded segment to the level of the superior mesenteric artery (SMA). Results. Only in 6 (17%) of 35 cases the narrowing portion of duodenum was located directly between aorta and SMA, and its length was about 1 cm. In the remaining 29 cases, the beginning of the narrow segment was 2.5–4.6 cm (average 3.30 ± 0.15 cm) proximal to SMA, ie, most of the narrowed duodenum was out of aortomesenteric angle. Location and length of the narrowed segment of duodenum corresponded to the location and length (3.2 ± 0.15 cm) (P>0.2) of the functional Ochsner sphincter. Conclusion. These data indicate that in most cases of SMAS the sphincter Ochsner dyskinesia causes the disease. It is likely that the disease is triggered by heavy stressful conditions that cause a sharp and sustained reduction in the pH of gastric secretions, which in turn leads to the spasms of the sphincter Ochsner. With time this condition progresses to hypertrophy of the contracted wall of the duodenum with subsequent replacement of the muscle fibers by connective tissue. This can lead to the rigidity of the wall.